Design, development, and evaluation of docetaxel-loaded niosomes for the treatment of breast cancer - Dipika S. Gaikwad; Rutuja D. Chougale; Kiran S. Patil; John I. Disouza; Ashok A. Hajare (SpringerOpen, 2023)
Abstract Background Docetaxel (DTX) has been used to treat numerous types of cancers. Poor solubility, lower bioavailability, and serious side effects limit its use in cancer treatment. The objective of the present research work was to develop DTX-loaded niosomes to overcome these issues and investigate the anticancer effect on breast cancer. Niosomes of DTX were prepared and evaluated to estimate particle size, surface potential, morphology by TEM, %EE, in vitro drug release, %hemolysis, in vitro cytotoxicity, and stability. The cytotoxicity effect of plain DTX and DTX-loaded niosomes was performed on MCF-7 cell lines. Results The mean particle size, zeta potential, and %EE of DTX-loaded niosomes were 244.9 nm, − 7.1 mV, and 97.43%, respectively. Besides, combining the DTX with polymers enhanced drug loading capacity. The TEM images confirmed spherical-shaped niosomes. The IR, DSC, and P-XRD studies indicate no chemical interaction between drug and excipients. The developed DTX niosomes showed a sustained release behavior and lower in vitro cytotoxicity when compared to plain DTX. Conclusion The current research work demonstrates the suitability of co-loading of DTX in niosomes as a promising approach to enhance the efficiency of DTX. Graphical Abstract